2006
DOI: 10.1021/la060933u
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Spherical Polyelectrolyte Brushes on Mica:  An in Situ AFM Investigation

Abstract: We demonstrate that the adsorption of cationic spherical polyelectrolyte brushes (SPB) on negatively charged mica substrates can be controlled in situ by the ionic strength of the suspension. The SPB used in our experiments consist of colloidal core particles made of polystyrene. Long cationic polyelectrolyte chains are grafted onto these cores that have diameters in the range of 100 nm. These particles are suspended in aqueous solution with a fixed ionic strength. Atomic force microscopy (AFM) in suspension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…While this has been demonstrated for hard particles 39 and soft shells,40 the present system could allow for annealing structures beca use of the stimuli-responsive nature of the brush layer, whieh avoids an irreversible hit-stick behaviour. 19 In addition, numerous chemical modifications have been reported for SPB particles ls . ' S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this has been demonstrated for hard particles 39 and soft shells,40 the present system could allow for annealing structures beca use of the stimuli-responsive nature of the brush layer, whieh avoids an irreversible hit-stick behaviour. 19 In addition, numerous chemical modifications have been reported for SPB particles ls . ' S .…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the force of adhesion could be adjusted by the ionic strength of the surrounding medium. 19 We extend these studies to substrates coated with charged polymers. Polyelectrolyte multilayers are applicable to almost any solid support and the layer-by-Iayer technique is compatible with 'a wide selection of polymers 21 The assembly process even allows the incorporation of charged particles opening avenues to highly functional surfaces.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Understanding the interaction of SPB with solid substrates is a prerequisite for their technological application in functional coatings. Studies with mica surfaces demonstrated distinct differences in the adsorption behavior of cationic and anionic SPB [34,35]. While anionic SPB exhibited a high lateral mobility on the negative substrates and Fig.…”
Section: Hanske Et Almentioning
confidence: 96%
“…Two approaches are chosen to investigate the adsorption of the two different types of SPB: In a first approach the negatively and positively charged particles adsorbed on mica were investigated by ex situ AFM techniques. In the second, in situ AFM experiments were carried out to investigate the adsorption and desorption of cationic particles on mica substrates in an aqueous environment (Gliemann et al, 2006;Mei et al, 2003). Table 6.1 summarizes the characteristic data of both SPB.…”
Section: Introductionmentioning
confidence: 99%